RESEARCH ON OPTIMAL DESIGN OF AL-ALLOYED CYLINDER HEAD UNDER HIGH LOADS - ZHANG QuanZhong; WEI ZhiMing; LIU ChangZhen; BAI JunAi; ZHANG Jie; MA JunHua (Jixie qiangdu)
With the increase of thermal and mechanical load of engine,the higher standards were required for materials,and the more serious challenges had been taken for the design technology. Based on simulation results of several cylinder heads,which had been strengthened,a relatively optimal frame cylinder head was obtained. The load carrying structures,which were interdependent,were included by bolt holes,the fuel injector holes,stiffeners of the top ceiling and the fire face. The results of reliability tests about mechanical fatigue and thermal fatigue revealed the structure of the Al- alloyed cylinder head under peak pressure（ 20 MPa） was reasonable.